PENDIDIKAN KARAKTER DI KUTTAB AL-FATIH KELURAHAN BULUSAN KECAMATAN TEMBALANG KOTA SEMARANG - Abrari Ilham (IAIN Manado, 2020)
This research aims to understand: 1 ) character education in Kuttab Al-Fatih Bulusan Village Tembalang District Semarang City especially relating to subject matter, method, evaluation 2 ) character education in the environment families in Kuttab Al-Fatih Bulusan Village Tembalang District Semarang City especially relating to, matter, method, evaluation.The research is the qualitative study descriptive with strategy used is a case study. The subject of study that became a source of data is: Kuttab Al-Fatih’s head master, teachers , learners, learners of parents, and Kuttab Al-Fatih’s website. The data collection is done with the interviews, observation, and documentation. To test the data validation was conducted by a test of triangulation .Data analysis used is the model descriptive analysis, eg the reduction of the data, presentation of data and the withdrawal of the conclusions.The result of this research concluded that character education in Kuttab Al-Fatih Bulusan Village Tembalang District Semarang City and family environment learners particularly subject matter, methods and evaluation. Subject matter covered aqidah development, worship, culture , akhlaq, intellectual, social, health and physical, environment, and technology. Method covered exemplary, patience, habituation, dialogue, the story, rewards, and integration. Evaluation in the environment Kuttab Al-Fatih Semarang covered reflection daily, absentee the presence of, and judgment culture, while in family environment covered the aspects of kognitig, affective, and psychomotor. The results of character education in Kuttab Al-Fatih Semarang have fullfilled eighteen (18) indicators like which was formulated by the Ministry Education and Culture Indonesian. But the authors founded nine (9) indicators values character that developed of them sincere, patient, the mandate, keep the promise, charity, good deeds, healthy life, friendly, and empathy. Of the total indicators values such characters, there are eleven (11) indicators character education who has attached to strong on each of students study : culture, religious, sincere, patient, honest, responsibility, discipline, socially responsible, caring environment, friendly, and healthy life. Eleven the education indicators character inherent strong on the self child who emerged as a significant element in integration pattern who built a between Kuttab Al-Fatih Semarang with parents learners